Removal of ethylene oxide from waste gases by absorption - Arsenijević Zorana Lj.; Grbavčić Željko B.; Grbić Boško V.; Radić Nenad D.; Garić-Grulović Radmila V.; Đuriš Mihal M. (Hemijska Industrija, 2011)
Ethylene oxide (EtO) is an organic compound, which is used as starting material in the production of polymers and as sterilizing agent for thermolabile materials. Although ethylene oxide is not common as an organic pollutant, its removal from numerous emission sources (e.g. ethylene oxide production plants or food and pharmaceutical sterilizing units) is of the crucial importance because of its mutagenic, teratogenic and cancerogenic effect on human health. The objective of this paper is the experimental investigation of ethylene oxide (EtO) absorption in diluted aqueous solution of sulfuric acid in order to evaluate the applicability of this procedure as well as to obtain project parameters for industrial plant realization. It was found that absorption is suitable as the fist step in the purification treatment of high EtO concentrations in the emission gases. According to the literature data, the basic parameter that defines the scrubber efficiency is the contact time, i.e. the ratio of packing height in scrubber and velocity of gas mixture. To investigate the characteristics of wet treatment in a broad range of contact time, part of experimental studies were conducted in the system with two and with three scrubbers in series. The obtained experimental results show that the high degree of EtO removal can be achieved (>98%) when the contact time is sufficiently long (about 25 s). The process is effective until the concentration of formed glycol in the solution reaches value of about 20%. The process is safe and there is no danger of ignition and explosion of air and EtO mixture, although at the entrance to the scrubber EtO concentrations are significantly above the lower explosive limit.